Practice of Contemporary Dance Improves Cognitive Flexibility in Aging - Coubard, Olivier A.; Duretz, Stéphanie; Lefebvre, Virginie; Lapalus, Pauline; Ferrufino, Lena (Frontiers in Aging Neuroscience, 2011)
As society ages and frequency of dementia increases exponentially, counteracting cognitive aging decline is a challenging issue for countries of the developed world. Previous studies have suggested that physical fitness based on cardiovascular and strength training helps to improve attentional control in normal aging. However, how motor activity based on motor-skill learning can also benefit attentional control with age has been hitherto a neglected issue. This study examined the impact of contemporary dance (CD) improvisation on attentional control of older adults, as compared to two other motor training programs, fall prevention and Tai Chi Chuan. Participants performed setting, suppressing, and switching attention tasks before and after 5.7-month training in either CD or fall prevention or Tai Chi Chuan. Results indicated that CD improved switching but not setting or suppressing attention. In contrast, neither fall prevention nor Tai Chi Chuan showed any effect. We suggest that CD improvisation works as a training for change, inducing plasticity in flexible attention.